Establishing assessment criteria for clinical reasoning in orthopedic manual physical therapy: a consensus-building study. (23rd February 2015) - Yeung, Euson; Woods, Nicole; Dubrowski, Adam; Hodges, Brian; Carnahan, Heather
<x content-type="archive" xml:space="preserve">Abstract</x> Objectives: Clinical reasoning (CR) represents one of the core components of clinical competence in Orthopaedic Manual Physical Therapy (OMPT). While education standards have been developed to guide curricular design, assessment of CR has not yet been standardized. Without theory-informed and rigorously developed measures, the certification of OMPTs lacks credibility and is less defensible. The purpose of this study was to use a theory-informed approach to generate assessment criteria for developing new assessment tools to evaluate CR in OMPT. Methods: A list of assessment criteria was generated based on international education standards and multiple theoretical perspectives. A modified Delphi method was used to gain expert consensus on the importance of these assessment criteria for the assessment of CR in OMPT. The OMPTs from 22 countries with experience in assessing CR were invited to participate in three rounds of online questionnaires to rate their level of agreement with these criteria. Responses were tabulated to analyze degree of consensus and internal consistency. Results: Representatives from almost half of the OMPT member organizations (MO) participated in three rounds of the Delphi. High levels of agreement were found among respondents regarding the importance and feasibility of most assessment criteria. There was high internal consistency among items within the proposed item subgroupings. Discussion: A list of assessment criteria has been established that will serve as a framework for developing new assessment tools for CR assessment in OMPT. These criteria will be important for guiding the design of certification processes in OMPT as well as other episodes of CR assessment throughout OMPT training.